Magnesium hydroxide nanoplate/graphene oxide composites as efficient adsorbents for organic dyes - Lee, Ju Ran; Bae, Ji Young; Jang, Wooree; Lee, Joong-Hee; Choi, Won San; Koo, Hye Young (ROYAL SOC CHEMISTRY, 2015)
Nanocomposites comprised of magnesium hydroxide (Mg(OH)(2)) and graphene oxide (GO) were prepared by the controlled precipitation of a magnesium salt on the GO surface. The population of Mg(OH)(2) nanocrystals on the GO surface could be varied by varying the Mg(OH)(2) precursor amount; the surface area of the resulting Mg(OH)(2)/GO nanocomposites varied from 75.2 m(2) g(-1) to 465 m(2) g(-1). The Mg(OH)(2)/GO nanocomposite with a surface area of 465 m(2) g(-1) showed the best performance. Owing to the synergistic effect of the nanoplate structure of Mg(OH)(2) and the 2D structure of GO, the obtained Mg(OH)(2)/GO nanocomposites exhibited high performance in methylene blue adsorption (adsorption capacity: 779.4 mg g(-1)).
Keywords: ADSORPTION; MG(OH)(2); REMOVAL